Determinants of infertility treatment from the point of couples referring to infertility treatment center in Southern Iran - Razie Toghroli; Maryam Azizi Kutenaee; Roghayeh Ezati Rad; Asiyeh Yari; Manoj Sharma (Scientific Reports)
Abstract Infertility and attempts to treat it are associated with stress for couples. In Iran, infertility is a problem associated with many challenges. The present study was conducted to Explaining effective factors of infertility treatment from the point of view of the participants of the infertility treatment center in Bandar Abbas City. This research is a qualitative content analysis research. The data were collected through in-depth semi-structured interviews with 36 men and women. A purposive sampling was used with maximum variety of Gender, Number of years of infertility, education, Economic situation different geographical regions and History of underlying disease. The interviews continued until data saturation. All the verbal interactions of the participants were recorded using a digital voice recorder and analyzed using qualitative-oriented content analysis. MAXQDA version 10 software was used to manage codes and facilitate data analysis. The average age of female participants was 36.5 and the average age of male participants was 41 years. Data analysis led to the identification of 7 main categories of determinants including (1) individual, (2) environmental, (3) religious, and psychological, (4) legal and regulatory, (5) socio-cultural, (6) economic s, and (7) therapeutic. Further, a total of 43 subcategories were identified. effective factors of infertility treatment identified in this study can help planners and policymakers in treating infertility and increasing the Iranian population which is on the decline.